"As if we were all struggling together": Black intellectual traditions and legacies of gendered violence. (November 2019) - Zellars, Rachel B.
Abstract: In North America, both Canada and the United States, violence against Black women has too often been historically displaced in the context of Black radical intellectual and organizing traditions. This paper attempts to account for the costs of this legacy and proposes a new model for Black intellectual traditions and organizing—that is, one that centres violence against women as a fundamental syntax within its organizing politic.